Evaluación del Tratamiento a Base Procaína Al 1% Como Alternativa en el Manejo del Dolor de Silla en Equinos De La Secretaría Distrital De Seguridad, Convivencia Y Justicia, Reporte De Caso (2023)
Neural therapy based on 1% procaine allows the functions of cell membranes and enzymes to be activated in the body; in this way, it is possible for the physiological functions to achieve their homeostasis quickly and without undesirable side effects. The research is carried out in horses belonging to the District Secretary for Security, Coexistence and Justice, focusing on animals previously diagnosed with interspinal thoracolumbar pain (saddle pain), in which the aforementioned therapy will be applied and the persistence of the pathology or its satisfactory evolution.